Development and characterization of benznidazole nano- and microparticles: A new tool for pediatric treatment of Chagas disease? - Seremeta, Katia Pamela (2019)
Benznidazole (BNZ) is the drug of choice for the treatment of Chagas disease in many countries. However, its low water solubility produces low and/or variable oral bioavailability. Thus, the aim of this work was to formulate micro- and nanoparticles based on Eudragit® RS PO and Eudragit® RL PO as a convenient approach to increase the dissolution rate of BNZ. The microparticles were obtained by means of spray-drying process while the nanoparticles were prepared through the nanoprecipitation technique and further freeze-drying. The results indicated that nanoparticles were obtained in 86% yield while microparticles were obtained in 68% yield. In both cases, the encapsulation efficiency of particles was greater than 78% while drug loading capacity was nearly 24% w/w and 18% w/w, after spray-drying and freeze-drying procedures, respectively. Images of scanning electron microscopy showed that the particles obtained by spray-drying and freeze-drying were in the micrometer and nanometer scale, respectively. FT-IR spectra of BNZ-loaded particles obtained by both methods showed characteristic bands of BNZ confirming that part of drug remained on their surface. Thermal analysis revealed that the drug crystallinity after both methods decreased. Physical stability evaluation of the nanoparticles confirmed that Pluronic® F68 was suitable to keep the particles size in a range of 300 nm after 70 days storage at 4 ± 2 °C. In-vitro release studies showed increased dissolution rate of drug from the particles obtained by both methods respect to untreated BNZ. The kinetics of drug release in acid media followed the Higuchi kinetics indicating drug diffusion mechanism from particles.